Allelic expression imbalance screening of genes in chromosome 1q21–24 region to identify functional variants for Type 2 diabetes susceptibility - Mondal, Ashis K. (American Physiological Society, 2013)
Type 2 diabetes (T2D)-associated SNPs are more likely to be expression quantitative trait loci (eQTLs). The allelic expression imbalance (AEI) analysis is the measure of relative expression between two allelic transcripts and is the most sensitive measurement to detect cis-regulatory effects. We performed AEI screening to detect cis-regulators for genes expressed in transformed lymphocytes of 190 Caucasian (CA) and African American (AA) subjects to identify functional variants for T2D susceptibility in the chromosome 1q21–24 region of linkage. Among transcribed SNPs studied in 115 genes, significant AEI (P < 0.001) occurred in 28 and 30 genes in CA and AA subjects, respectively. Analysis of the effect of selected AEI-SNPs (≥10% mean AEI) on total gene expression further established the cis-eQTLs in thioesterase superfamily member-4 (THEM4) (rs13320, P = 0.027), and IGSF8 (rs1131891, P = 0.02). Examination of published genome-wide association data identified significant associations (P < 0.01) of three AEI-SNPs with T2D in the DIAGRAM-v3 dataset. Six AEI single nucleotide polymorphisms, including rs13320 (P = 1.35E-04) in THEM4, were associated with glucose homeostasis traits in the MAGIC dataset. Evaluation of AEI-SNPs for association with glucose homeostasis traits in 611 nondiabetic subjects showed lower AIR(G) (P = 0.005) in those with TT/TC genotype for rs13320. THEM4 expression in adipose was higher (P = 0.005) in subjects carrying the T allele; in vitro analysis with luciferase construct confirmed the higher expression of the T allele. Resequencing of THEM4 exons in 192 CA subjects revealed four coding nonsynonymous variants, but did not explain transmission of T2D in 718 subjects from 67 Caucasian pedigrees. Our study indicates the role of a cis-regulatory SNP in THEM4 that may influence T2D predisposition by modulating glucose homeostasis.